Determinants of the Quality of Life for Hemodialysis Patients - Pratiwi, Danies Tunjung; Tamtomo, Didik Gunawan; Suryono, Arief (Indonesian Journal of Medicine, 2019)
Background: Chronic kidney disease (CKD) is a major cause of changes in activity, psychology and life. Analysis of the use of hemodialysis on quality of life was carried out as a treatment evaluation to maintain the survival of CKD patients. This study aimed to determine the determinants quality of life among hemodialysis patients.Subjects and Method: This was a cross-sectional study conducted at the Hospital Hemodialysis Unit Dr. Hardjono, Ponorogo, East Java, in April 2019. A total sample of 200 hemodialysis patients were selected using simple random sampling. The dependent variable was the quality of life of hemodialysis patients. The independent variables were age, gender, education, type of financing, family income, stress, frequency of hemodialysis, level of physical dependence, comorbidity, and social group. The data of life quality were collected using the Kidney Disease Quality of Life (KDQoL) SF-36 questionnaire and analyzed using multiple logistic regressions.Results: The quality of life of hemodialysis patients was affected by age ≥ 50 years (b = -1.40; CI 95% = -2.42 to -0.36; p = 0.008), severe stress (b = -1.73; CI 95% = -2.91 to -0.54; p = 0.004), had comorbidity (b = -1.25; CI 95% = -2.29 to -0.23; p = 0.017), male sex (b = 1.48; CI 95% = 0.41 to 2.54; p = 0.007), education high (b = 1.46; 95% CI = 0.43 to 2.50; p = 0.006), family income ≥ minimum wage (b = 1.98; 95% CI = 0.75 to 3.20; p = 0.002), PBI financing type (b = 1.69; 95% CI = 0.40 to 2.98; p = 0.010), frequency of hemodialysis often (b = 1.21; 95% CI = 0.20 to 2.22; p = 0.019), independent physical dependence level (b = 1.41; 95% CI = 0.33 to 2.49 ; p = 0.011), and has a social group (b = 3.28; 95% CI = 1.12 to 9.65; p = 0.031).Conclusions: Age, gender, education, type of financing, family income, stress, frequency of hemodialysis, level of physical dependence, comorbidity, and social group affect the quality of life of hemodialysis patients.Keywords: Chronic kidney disease, quality of life, hemodialysis, social group.Correspondence: Danies Tunjung Pratiwi. STIKES Buana Husada, Jl. Gabah Sinawur 9A, Ponorogo 63411, Jawa Timur. Email: daniestunjung@gmail.com. Mobile: +6285229-209108Indonesian Journal of Medicine (2019), 4(2): 145-154https://doi.org/10.26911/theijmed.2019.04.02.08